PERBANDINGAN ANTARA SEKOLAH SWASTA DAN NEGERI DI PROVINSI SUMATERA UTARA, INDONESIA: SYSTEMATIC LITERATURE REVIEW - Irma Pratiwi (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2023)
This study aims to compare private and public schools in North Sumatra Province, Indonesia, using the Systematic Literature Review (SLR) method. The research analyzes relevant literature to identify factors influencing school choice by parents and students and compares academic performance, facilities, and teaching quality between private and public schools. The findings of this study are expected to provide insights for education policymakers and parents in making decisions related to school selection.